Rapid photooxidation of Sb(III) in the presence of different Fe(III) species. (1st May 2016) - Kong, Linghao; He, Mengchang; Hu, Xingyun
Abstract: The toxicity and mobility of antimony (Sb) are strongly influenced by the redox processes associated with Sb. Dissolved iron (Fe) is widely distributed in the environment as different species and plays a significant role in Sb speciation. However, the mechanisms of Sb(III) oxidation in the presence of Fe have remained unclear because of the complexity of Fe and Sb speciation. In this study, the mechanisms of Sb(III) photooxidation in the presence of different Fe species were investigated systematically. The photooxidation of Sb(III) occurred over a wide pH range, from 1 to 10. Oxygen was not a predominant or crucial factor in the Sb(III) oxidation process. The mechanism of Sb(III) photooxidation varied depending on the Fe(III) species. In acidic solution (pH 1–3), dichloro radicals ( Cl2 − ) and hydroxyl radicals ( OH) generated by the photocatalysis of FeCl 2+ and FeOH 2+ were the main oxidants for Sb(III) oxidation. Fe(III) gradually transformed into the colloid ferric hydroxide (CFH) and ferrihydrite in circumneutral and alkaline solutions (pH 4–10). Photooxidation of Sb(III) occurred through electron transfer from Sb(III) to Fe(III) along with the reduction of Fe(III) to Fe(II) through a ligand-to-metal charge-transfer (LMCT) process. The photocatalysis of different Fe(III) species may play an important role in the geochemical cycle of Sb(III) in surface soil and aquatic environments.